2019
DOI: 10.1590/fst.34417
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hot air, vacuum and microwave drying on drying characteristics, rehydration capacity, color, total phenolic content and antioxidant capacity of Kumquat (Citrus japonica)

Abstract: Sliced kumquats were dried by using three different drying methods, microwave (375 W), hot air (70 and 80 °C), and vacuum (70 and 80 °C with 100 and 300 mbar) to determine drying characteristics, antioxidant capacity and total phenolic content and color. All color parameters (L, a, b, C ab , ΔE and h°) changed depending on the drying methods. Page and Modified Page models are the best fitted drying methods with the highest value of R 2 (0.9994) and the lowest values of RMSE (0.000635-0.000735) and χ 2 (0.00001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 50 publications
6
32
0
Order By: Relevance
“…The reason for this observation may be stated as the water molecules penetrate through the void spaces created by microwave within the adjoining cell. A similar observation was reported by Ozcan-sinir et al [22]. MWC being the fastest drying method employed for pineapple slices in this study, resulted in irreversible cellular shrinkage, which may responsible for hindrance in water uptake during rehydration operation.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The reason for this observation may be stated as the water molecules penetrate through the void spaces created by microwave within the adjoining cell. A similar observation was reported by Ozcan-sinir et al [22]. MWC being the fastest drying method employed for pineapple slices in this study, resulted in irreversible cellular shrinkage, which may responsible for hindrance in water uptake during rehydration operation.…”
Section: Resultssupporting
confidence: 91%
“…Therefore it is necessary to know which factors control these properties. Rehydration characteristics have been found to be a crucial factor in controlling these properties of dried product [22]. In consequences of moisture removal during the drying period, the capillary space became narrow, shrinkage of cells occurred and moreover, the contraction was observed in cellular material which leads to disintegrating the vegetal tissue.…”
Section: Resultsmentioning
confidence: 99%
“…The TPC content of fresh orange slices (1,238.04 mg GAE/100 g dw) was much lower than the value of 23,250 mg GAE/100 g reported by Ghasemi, Ghasemi, and Ebrahimzadeh (2009) for orange tissue extract powder. However these results were in line with results reported by Rahman, Shamsudin, Ismail, Shah, and Varith (2018) for pomelo ( Citrus grandis [L.] Osbeck) lamella peels as 1,198.85 mg GAE/100 g dw and exceeding those reported by Ozcan‐Sinir et al (2019) as 266.68 mg GAE/100 g dw. for kumquat ( Citrus japonica ) slices.…”
Section: Resultssupporting
confidence: 91%
“…It means that dried orange slices were significantly ( p < .05) darker than fresh sample and VD at 70°C 30 kPa application showed the lowest L* value. These findings were similar with Ozcan‐Sinir, Ozkan‐Karabacak, Tamer, and Çopur (2019) who reported that L* values of dried kumquats ( citrus japonica ) were reduced when compared with fresh sample. Moreover Garau, Simal, Rosello, and Femenia (2007) found L* values of fresh orange peels and pulps as 86.02 and 86.30, respectively and observed a reduction after drying with different temperatures ranged 6.87% to 8.67% and 5.98% to 13.27%, respectively.…”
Section: Resultssupporting
confidence: 89%
“…The products dried using low-pressure superheated drying had higher retention of ascorbic acid, β-carotene, total phenol content, compared to those produced by using vacuum drying and hot air drying. Dzcan-Sinir et al (2019) revealed that microwave dried kumquat slices had the highest antioxidant activity among microwave (375 W), hot air (70 and 80 °C), and vacuum drying. The high-quality products of instant food require the unique taste of the white fungus, but also preserve the nutrients of the white fungus.…”
Section: Introductionmentioning
confidence: 99%